THYMIDINE TRIPHOSPHATE SYNTHESIS IN TETRAHYMENA : I. Studies on Thymidine Kinase - Shoup, G. D. (The Rockefeller University Press, 1966)
The amount of thymidine-H(3) converted to thymidine-H(3) monophosphate in 30 min formed the basis for assays of thymidine kinase in cell extracts from Tetrahymena pyriformis. The optimal concentration of adenosine triphosphate is lower than that required by other cell types. Thymidine triphosphate does not exercise any feedback control of the enzyme. Other deoxyprimidine nucleotides were tested, but these also failed to exhibit any feedback inhibition. At suboptimal adenosine triphosphate levels, thymidine triphosphate and other deoxypyrimidine nucleotides stimulate the reaction, suggesting that these nucleotides may act either directly or indirectly as phosphate donors in the crude enzyme preparations. This possibility was affirmed when thymidine triphosphate and deoxycytidine triphosphate were shown to be capable of limited phosphorylation of thymidine. Comparison of enzymatic activities in logarithmically growing culture and stationary phase culture, in which nuclear DNA synthesis has virtually ceased, reveals no change in enzymatic activity. The results suggest that thymidine kinase is a constitutive enzyme in Tetrahymena.